Recovery of Wakaf Assets Post Natural Disasters according to Islamic Law and Positive Law - Siska Lis Sulistiani; Intan Nurrachmi; Ramdan Fawzi (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
This study aims to ascertain and evaluate the processes followed by national and Islamic law to recover waqf assets following a calamity. The 1945 Constitution, Law No. 41 of 2004 on Waqf, and other regulations are among the key legal data sources used in this qualitative study employing a normative juridical method from the viewpoint of Islamic law, which is derived from the Quran, the Hadith, and the views of relevant scholars. Periodicals and other pertinent articles are examples of secondary legal sources. Next, using descriptive analytic techniques, the data was gathered through library research and examined to determine the synchronization stage and compliance with legal norms and principles. The study's findings demonstrate that waqf assets—such as damaged land and buildings—can be recovered. In Islamic law, as long as there is no proof of someone's ownership, the assets return to the state. This is almost the same as positive law in Indonesia, namely if the affected waqf assets are destroyed or damaged and previously had a waqf certificate, efforts can be made to identify the waqf assets, and if important files related to the waqf are lost, you can contact BPN to get a copy, but if the assets are destroyed according to the UUPA the land returns to the state. Financing can be done by optimizing the funding of cash waqf and cash waqf for efforts to repair and rebuild these assets.